The Correlation between Self-Esteem and Speaking Skill of the Seventh-Grade in Junior High School - Fitri Widiani, Ni Kadek; Ari Wiryadi Joni, Dewa Ayu; Istri Yudhi Pramawati, Anak Agung (Journal on Studies in English Language Teaching (JOSELT), 2024)
Speaking is a complex aspect of communication, requiring practice and exposure. Self-esteem, representing individuals' beliefs in their worth and abilities, influences how students perform in speaking tasks. The primary goal of this study was to find the correlation between self-esteem and speaking skill. The subject in this study was the seventh-grade students of SMPN 4 Denpasar in the academic year 2023/2024. The sample consisted of 50 students from the seventh-grade. The researchers used two tests to collect data: descriptive monologue test, and questionnaire. The data were analyzed using pearson product moment correlation assissted with SPSS 25.0 version. It was found out that there was a significant correlation between self-esteem and speaking skill of the seventh-grade students of SMPN 4 Denpasar in the academic year 2023/2024. This study provides empirical evidences of the correlation between self-esteem and students’ speaking skill in secondary level.